2013
DOI: 10.5798/diclemedj.0921.2013.03.0290
|View full text |Cite
|
Sign up to set email alerts
|

Common pathogens isolated from burn wounds and their antibiotic resistance patterns

Abstract: Objective: Burn wound infections are the most severe cause of mortality in patients in the burn units. The aim of this study is to determine the bacteriological profile and their antibiotic resistance patterns in burn unit of Dicle University Hospital. Methods: Medical records of 151 burn patients admitted to the burn unit of Dicle University Hospital between June, 2008 and June 2010 were reviewed retrospectively. Results: Our study included 70.2% (n=106) male and 29.8% (n=45) female patients. The mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The incidence of P. aeruginosa infection was higher in men than in females, 42 (56%) and 33 (44%) respectively. The results of the current study agree with the study of (15) of bacteria isolated from burn patients, which showed that the percentage of males was (77%) and females (23%), and also agrees with the study (Yolbaş et al, 2013), where This study showed infection rate for males (70%) and females (30%).…”
Section: 7supporting
confidence: 92%
“…The incidence of P. aeruginosa infection was higher in men than in females, 42 (56%) and 33 (44%) respectively. The results of the current study agree with the study of (15) of bacteria isolated from burn patients, which showed that the percentage of males was (77%) and females (23%), and also agrees with the study (Yolbaş et al, 2013), where This study showed infection rate for males (70%) and females (30%).…”
Section: 7supporting
confidence: 92%
“…Results and Discussion The incidence of P. aeruginosa infection was higher in men than in females, 42 (56%) and 33 (44%) respectively. The results of the current study agree with the study of (AL-Shamaa et al, 2016) of bacteria isolated from burn patients, which showed that the percentage of males was (77%) and females (23%), and also agree with the study (Yolbaş et al, 2013), where This study showed infection rate for males (70%) and females (30%).…”
supporting
confidence: 93%
“…The findings were in accordance with various studies. 16,18 The percentage of colonization by Staphylococcus aureus did not show much change in the periodic samples. The persistence of Staphylococcus throughout our study could be due to cross-infection of micro-organisms in ICU.…”
Section: Discussionmentioning
confidence: 93%
“…15 Regarding growth of Acinetobacter baumanni, it was similar to other studies who also reported higher frequency of Acinetobacter infections. 16 Acinetobacter baumannii is a rapidly emerging pathogen in the health care setting, where it causes infections that include bacteremia, pneumonia, meningitis, urinary tract infection, and wound infection. The organism's ability to survive under a wide range of environmental conditions and to persist for extended periods of time on surfaces make it a frequent cause of outbreaks of infection and an endemic, health care-associated pathogen.…”
Section: Discussionmentioning
confidence: 99%